2018
DOI: 10.1002/chem.201804714
|View full text |Cite
|
Sign up to set email alerts
|

London Dispersion Interactions in Pnictogen Cations [ECl2]+ and [E=E]2+ (E=P, As, Sb) Supported by Anionic N‐Heterocyclic Carbenes

Abstract: Several pnictogen dihalide complexes of the type (WCA‐IDipp)EX2 (E=P, As, Sb; X=Cl, Br) that bear an anionic N‐heterocyclic carbene ligand with a weakly coordinating borate moiety (WCA‐IDipp, WCA=B(C6F5)3, IDipp=1,3‐bis(2,6‐diisopropylphenyl)imidazolin‐2‐ylidene) were prepared by salt metathesis reactions between the respective pnictogen trihalides EX3 and the lithium salt (WCA‐IDipp)Li⋅toluene. Two‐electron reduction of the dihalides (WCA‐IDipp)EX2 with 1,3‐bis(trimethylsilyl)‐1,4‐dihydropyrazine or elemental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 121 publications
(352 reference statements)
3
44
0
Order By: Relevance
“…They observed that, if functionals like BLYP or B3LYP are used, the magnitude of the D3 correction is close to the LED estimate of the dispersion energy in a large variety of cases. These findings are consistent with previous results from our group . However, the agreement between D3 and LED dispersion is of course not universally valid and there are notable exceptions …”
Section: Coupled Cluster Analyses Of Noncovalent Interactionssupporting
confidence: 90%
See 1 more Smart Citation
“…They observed that, if functionals like BLYP or B3LYP are used, the magnitude of the D3 correction is close to the LED estimate of the dispersion energy in a large variety of cases. These findings are consistent with previous results from our group . However, the agreement between D3 and LED dispersion is of course not universally valid and there are notable exceptions …”
Section: Coupled Cluster Analyses Of Noncovalent Interactionssupporting
confidence: 90%
“…For instance, this partitioning can be used to discuss intramolecular interactions or, more generally, any interaction for which single point energies on the isolated fragments are not feasible. Above all, the LED scheme has found widespread applications in the analysis of strong and weak intermolecular interactions within a supermolecular approach …”
Section: Coupled Cluster Analyses Of Noncovalent Interactionsmentioning
confidence: 99%
“…S3†). Notably, Tamm and co-workers recently reported on the isolation of a diphosphene derivative obtained by the reduction of related dichlorophosphane with compound 6 21. The 31 P NMR spectrum of the reaction mixture shows only one major prominent intermediate with a singlet resonance at δ (P) = –29.1 ppm, which is in the range for diphosphanes 22.…”
Section: Resultsmentioning
confidence: 99%
“…Facile reactions of PCl 3 , PBr 3 , SbCl 3 and AsCl 3 with Li/NHC adducts 44 afford the corresponding P–NHC, Sb–NHC and As–NHC products 45 ( Scheme 9 ). 110 …”
Section: Organometallic Chemistry Behind the H–nhc C–nhc And X–nhc Cmentioning
confidence: 99%